Analysis of determination of rabies virus neutralizing antibody titres in the sera of vaccinated humans - A. Yu. Butirskiy; A. V. Muhacheva; A. A. Movsesyants; K. A. Sarkisyan (Вопросы вирусологии, 2019)
Introduction. Rabies is an infectious disease that is always fatal following the onset of clinical symptoms. The only way to prevent the cases of rabies in humans is timely carried out the rabies post-exposure prophylaxis in accordance with the recommended schedule. The aim of the study was to characterize the level of immune response in persons that received a post-exposure prophylaxis against rabies, to consider the role of the factors of the formation immune responses to rabies vaccines . Material and methods. In the laboratory of viral vaccines of the Scientific Centre for Expert Evaluation of Medicinal Products, the 48 sera of patients that received the post-exposure prophylaxis of rabies after wounds from a rabid or suspected rabid animal has been studied. The titer of virus neutralizing antibodies (VNA) to the rabies virus in the sera of the vaccinated not less than 1:64 (corresponding to a level of VNA at least 0,5 IU /ml) in the mouse neutralization test indicates the effective vaccination. Results and discussion. Our data confirm the absence of statistically significant differences in the level of VNA in the vaccinated persons that received a complete and incomplete (5 doses) course of post-exposure vaccination against rabies. Depending on the level of VNA, all patients are divided into groups with conditionally low, medium and high content of antibodies in sera. Conclusion. It has been shown that in most cases properly administered vaccination contributed to the formation of effective immune response. The lack of a protective level of BHA requires additional administration of the vaccine and analysis of the factors that influenced the ineffectiveness of vaccination. In some patients the determination of rabies virus neutralizing antibody titres is necessary.